MesoRAD: A New Radiocarbon Data Set for Archaeological Research in Mesoamerica. (21st December 2021) - Hoggarth, Julie A.; Ebert, Claire E.; Castelazo-Calva, Victor E.
The Mesoamerican Radiocarbon Database (MesoRAD) compiles radiocarbon dates from the archaeological literature of Mesoamerica. The inaugural data set, 'Lowland Maya Dates', includes 1846 radiocarbon dates from 132 sites in 21 distinct environmental zones in the Maya lowlands. These data span the Paleoindian to Colonial Periods (11, 670 to 190 uncal BP, 13, 740 cal BP to modern) across southern Mexico, Belize, Guatemala, El Salvador, and Honduras. Here, we describe the methods used to compile and organize these dates, including the spatial, chronological, and environmental coverage of the data set.